Addition of H2 Across a Cobalt–Phosphorus Bond. (11th January 2018) - Poitras, Andrew M.; Knight, Sadie E.; Bezpalko, Mark W.; Foxman, Bruce M.; Thomas, Christine M.
Abstract: Addition of H2 across the cobalt–phosphorus bond of (PPP)CoPMe3 (3 ) is demonstrated, where PPP is a monoanionic diphosphine pincer ligand with a central N‐heterocyclic phosphido (NHP − ) donor. The chlorophosphine Co II complex (PP Cl P)CoCl2 (2 ) can be generated through coordination of the chlorophosphine ligand (PP Cl P, 1 ) to CoCl2 . Subsequent reduction of2 with KC8 in the presence of PMe3 generates (PPP)CoPMe3 (3 ), in which both the phosphorus and cobalt centers have been reduced. The addition of 1 atm of H2 to complex3 cleanly affords (PP H P)Co(H)PMe3 (4 ), in which H2 has ultimately been added across the metal–phosphorus bond. Complex4 was characterized spectroscopically and using computational methods to predict its geometry.